Os espaços livres nas zonas especiais de interesse social: um estudo no bairro Jesus de Nazareth, Vitória, Espírito Santo - Santana, Elaine Cristine Santos (2019)
The Special Zones of Social Interest (ZEIS) were established in urban planning as an instrument of public policy to encourage land and urban regularization of irregular occupations. It is common in these areas the lack of open spaces with adequate infrastructure and equipment for leisure activities, sports and socialization. It starts from the hypothesis that open spaces can be adopted as an urban planning strategy to promote the socio-spatial development of ZEIS, on the assumption that these are more democratic, as they are accessible to citizens, providing greater opportunities for appropriation and transformation. The Jesus de Nazareth neighborhood is the object of study of field research, which aimed to investigate open spaces in the context of a ZEIS, from the evaluation of its most significant attributes in terms of socio-environmental, landscape, urban planning, and sociocultural aspects, to reflect on how they can contribute to local socio-spatial development. From the bibliographic research, a set of existing methods and criteria for the evaluation and spatial analysis were adopted in the empirical research, for the local recognition, through the mapping focused on the qualitative analysis based on quantitative data, questionnaires, interviews and workshops. This composition adapted to the particularities of a ZEIS resulted in a unique methodology, which was presented as a differential of this research. The results showed that the community of Jesus de Nazareth has appropriated its open spaces as a socio-spatial development strategy, even with autonomous and punctual actions. It is necessary a change of perspective in the reading and study of the spaces of the city, and the improvement of methodological tools, mainly, of representation forms capable of artistically and symbolically synthesizing their immaterial information, intending to bring contributions to the socio-spatial development process.